2024
DOI: 10.1024/0300-9831/a000771
|View full text |Cite
|
Sign up to set email alerts
|

CD36 polymorphism, sugary drinks, and sedentarism are associated with hypertriglyceridemic waist phenotype

Abstract: Abstract. Background: The hypertriglyceridemic waist (HTGW) phenotype is characterized by concomitant increases in waist circumference (WC) and blood triglyceride levels (TG), which has been identified as a predictor of metabolic disorders. This study aimed to analyze associations between food consumption, exercise, and the CD36 gene rs1761667 G>A polymorphism with the HTGW phenotype in adult Mexicans. Methods: This cross-sectional study included a total of 255 participants (both genders, between 18–64 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that CD36 polymorphisms are correlated with metabolic dysregulation [49]. Studies about the interaction between CD36 rs1761667 and diet are rare, for example, Navarro-Rios et al [50] showed that daily consumption of sugary drinks can be a risk factor for hypertriglyceridemic waist phenotype (as a predictor of metabolic disorders) in the AG genotype of the rs1761667 polymorphism, while Lopez-Ramos et al [23] observed that individuals with the AA genotype of CD36 rs1761667 had a higher intake of total fat, polyunsaturated fatty acids, MUFA, and saturated fatty acids. Furthermore, the serum cholesterol level in this genotype group was significantly higher than AG genotype carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CD36 polymorphisms are correlated with metabolic dysregulation [49]. Studies about the interaction between CD36 rs1761667 and diet are rare, for example, Navarro-Rios et al [50] showed that daily consumption of sugary drinks can be a risk factor for hypertriglyceridemic waist phenotype (as a predictor of metabolic disorders) in the AG genotype of the rs1761667 polymorphism, while Lopez-Ramos et al [23] observed that individuals with the AA genotype of CD36 rs1761667 had a higher intake of total fat, polyunsaturated fatty acids, MUFA, and saturated fatty acids. Furthermore, the serum cholesterol level in this genotype group was significantly higher than AG genotype carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for exercise assessment, participants were asked if they regularly practiced some type of systematic physical exercise or sport (yes/no) at least 150-300 min a week, as described elsewhere [30].…”
Section: Dietary Intake and Physical Exercisementioning
confidence: 99%